Putative Virulence Factor Expression by Clinical and Food Isolates of Bacillus spp. after Growth in Reconstituted Infant Milk Formulae - Rowan, Neil J. (American Society for Microbiology, 2001)
Forty-seven strains representing 14 different Bacillus species isolated from clinical and food samples were grown in reconstituted infant milk formulae (IMF) and subsequently assessed for adherence to, invasion of, and cytotoxicity toward HEp-2 and Caco-2 cells. Cell-free supernatant fluids from 38 strains (81%) were shown to be cytotoxic, 43 strains (91%) adhered to the test cell lines, and 23 strains (49%) demonstrated various levels of invasion. Of the 21 Bacillus cereus strains examined, 5 (24%) were invasive. A larger percentage of clinically derived Bacillus species (20%) than of similar species tested from the food environment were invasive. Increased invasion occurred after growth of selected Bacillus species in reconstituted IMF containing glucose. While PCR primer studies revealed that many different Bacillus species contained DNA sequences encoding the hemolysin BL (HBL) enterotoxin complex and B. cereus enterotoxin T, not all of these isolates expressed these diarrheagenic genes after growth in reconstituted IMF. Of the 47 Bacillus isolates examined, 3 isolates of B. cereus and 1 isolate of B. subtilis produced the HBL enterotoxin after 18 h of growth in brain heart infusion broth. However, eight isolates belonging to the species B. cereus, B. licheniformis, B. circulans, and B. megaterium were found to produce this enterotoxin after growth in reconstituted IMF when assessed with the B. cereus enterotoxin (diarrheal type) reversed passive latex agglutination (RPLA) kit. It is concluded that several Bacillus species occurring occasionally in clinical specimens and food samples are of potential medical significance due to the expression of putative virulence factors.